Analisis Pola Radiasi Antena Dipole pada aplikasi Wireless Sensor Networks di Industrial Site - Nabila Husna Shabrina; Samuel Samuel (Ultima Computing : Jurnal Sistem Komputer, 2018)
In industry 4.0, a complex system was needed to automatically control and communicate between devices. One component that often used in industrial automation is Wireless Sensor Networks (WSN), which is worked by transmitting the data needed through electromagnetic waves. The electromagnetic propagation in industrial process encounter challenges which caused by reflection or scattering from the object inside the industrial site. Therefore, in this research, the author will conduct a simulation to determine the characteristic of electromagnetic propagation in industrial site. The simulation was done by simulating antenna dipole with frequency 2.4 GHz in the simple 3D industrial site consist of some component. The result shows that simulating antena dipole in industrial site will affect the characteristic of the antena such as gain, directivity, and S parameter.